2023
DOI: 10.3390/insects14050448
|View full text |Cite
|
Sign up to set email alerts
|

Trade-Offs between Temperature and Fitness in Euschistus heros (Fabricius) (Hemiptera: Pentatomidae): Implications for Mass Rearing and Field Management

Abstract: The brown stink bug, Euschistus heros (Fabricius, 1798) (Hemiptera: Pentatomidae), is one of the most abundant soybean stink bug pests in Brazil. Temperature is a key factor that affects its development and reproduction, and fluctuating temperatures may impact the development and reproduction of E. heros differently from those under constant temperatures. The objective of this study was to evaluate the influence of constant and fluctuating temperature on the biological characteristics of E. heros in three succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…The number of eggs offered (about 1890 eggs per plot), the time allowed for parasitism (24 h) and the use of cryopreserved eggs as sentinels might also explain the low parasitism rate observed. The number of eggs and distance might exceed T. podisi ’s parasitism capacity in 24 h. Although in applied inundative biological control programs, the parasitism capacity holds greater significance than the lifespan of females in the field [ 8 ], T. podisi females might have needed more than 24 h for the pre-reproductive period to reach its full parasitism capacity in the field [ 34 ]. Bueno et al [ 2 ] reported a 70% parasitism rate in soybean fields after T. podisi release; however, this was after three parasitoid releases and over a period of 27 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of eggs offered (about 1890 eggs per plot), the time allowed for parasitism (24 h) and the use of cryopreserved eggs as sentinels might also explain the low parasitism rate observed. The number of eggs and distance might exceed T. podisi ’s parasitism capacity in 24 h. Although in applied inundative biological control programs, the parasitism capacity holds greater significance than the lifespan of females in the field [ 8 ], T. podisi females might have needed more than 24 h for the pre-reproductive period to reach its full parasitism capacity in the field [ 34 ]. Bueno et al [ 2 ] reported a 70% parasitism rate in soybean fields after T. podisi release; however, this was after three parasitoid releases and over a period of 27 days.…”
Section: Discussionmentioning
confidence: 99%
“…Populations of E. heros are affected by diseases, other natural enemies [ 41 , 42 , 43 , 44 ] and by abiotic factors [ 45 ]. Barrufaldi et al [ 34 ] documented 40% mortality just from molting in E. heros with the highest mortality occurring between the first and second-stage nymphs. At these stages, the stink bug does not compromise soybean yield or quality [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…We determined the effects of temperature on life history using constant temperatures maintained in the growth chambers for each temperature rather than in replicated chambers. Previous studies have demonstrated the potential limitation of this approach and additional assessment and refinement of temperature requirements, including the effects of fluctuating temperatures on HGA development, is warranted [48].…”
Section: Discussionmentioning
confidence: 99%